Perlindungan Hukum Terhadap Pihak Ketiga Akibat Direksi Melakukan Tindakan di Luar Anggaran Dasar Perseroan Terbatas - Putu Agung Surya Prawira; I Nyoman Putu Budiartha; Ni Made Puspa Sutariujianti (Warmadewa Press, 2021)
Company carrying out actions outside the articles of association can basically be explained from the idea that the principles outside of these articles of association are generally accepted doctrines. In this case, sometimes there are problems that occur, so legal protection for third parties is very necessary in overcoming actions outside the articles of association of the limited liability company. The purpose of this study is to reveal the legal protection of third parties in the case of directors taking actions outside the articles of association of a limited liability company in an effort to restore the rights of third parties for actions by directors outside the articles of association of a limited liability company (PT). The type of research applied in this research is normative research. The sources of legal materials used are primary and secondary legal sources. Techniques for collecting legal materials by studying document recording. After the legal material is collected, it is then analyzed qualitatively. The results of the study reveal that in Indonesia it is possible to implicitly state the Limited Liability Company Law, acknowledge and accept the Doctrine outside the articles of association of the Limited Liability Company. In addition, there are also some grounds that can be used as an alibi to provide protection against third parties. These basics include the Principle of Good Faith, the Pacta Sun Servanda Principle and the Doctrine outside the Modern constitution. By relying on these basics, preventive legal protection and repressive legal protection can be provided.